Febuxostat in the therapy of gout: from theory to practice - E. V. Ilyinykh; S. A. Vladimirov; M. S. Eliseev (Современная ревматология)
Gout is a chronic disease that requires permanent urate-lowering therapy. Allopurinol is the gold standard of this therapy. The novel drug febuxostat, a selective xanthine oxidase inhibitor, has been synthesized and introduced into clinical practice in the last 10 years. The paper reviews the literature on the main clinical trials of febuxostat, which show its efficacy that is comparable to or more higher than that of allopurinol, as well as the possibility of using this drug for reduced kidney function, allergic reaction to allopurinol or resistance to therapy with allopurinol, which considerably improves prognosis in these patients. The long-term use of febuxostat is noted to result in almost complete resorption of tophi and in termination of gouty arthritis attacks. These findings allow febuxostat to be considered as a promising and essential medication for the treatment of gout. Great hopes are pinned on the extension of its application; there are ongoing investigations regarding the possibility of using this drug for asymptomatic hyperuricemia and other conditions accompanied by higher uric acid levels.